Transarterial Chemoembolization Combined With Radiofrequency Ablation Versus Hepatectomy for Hepatocellular Carcinoma: A Meta-Analysis - Dan, Yuan; Meng, Wenjun; Li, Wenke; Chen, Zhiliang; Lyu, Yongshuang; Yu, Tianwu (Frontiers in Surgery, 2022)
Background Although many studies reported the effectiveness of transarterial chemoembolization (TACE) combined with radiofrequency ablation (RFA) or surgical resection (SR) in the treatment of hepatocellular carcinoma (HCC), the efficacy of these two strategies remains controversial. Therefore, this meta-analysis aimed to evaluate and compare the efficacy of sequential use of TACE plus RFA (TACE + RFA) and SR alone in treating HCC. Methods Relevant studies with unmatched and propensity score-matched patients were identified by comprehensive search of MEDLINE, PubMed, EMBASE, Web of Science, and Cochrane electronic databases. Meta-analysis was conducted using Review Manager (RevMan) software version 5.4.1. Finally, 12 eligible studies were included in this study, including 11 case–control studies and 1 randomized controlled trial. The primary outcome of interest for this study was to compare the 1-, 3-, and 5-year overall survival (OS) and disease-free survival (DFS), major complications, 5-year OS in different tumor diameters between the two treatment strategies, and hospital stay time. Results HCC patients who received TACE + RFA had a lower incidence of complication rates and shorter hospital stay time than those who received SR alone. Among these studies using propensity score-matched cohorts, SR had better 3- and 5-year OS than TACE + RFA, whereas there were no significant differences between TACE + RFA and SR regarding the 1-, 3-, and 5-year DFS. When the tumor diameter is longer than 3 cm, the 5-year OS rate is better when SR is selected. Conclusion There was no significant difference in the short-term survival outcomes between TACE + RFA and SR in HCC patients. Moreover, SR is superior to TACE + RFA in terms of long-term beneficial effects but may result in a higher risk of major complications and a longer hospital stay time.